2001
DOI: 10.1006/anbe.2001.1825
|View full text |Cite
|
Sign up to set email alerts
|

Is cricket courtship song condition dependent?

Abstract: Females of the Texas trilling field cricket, Gryllus texensis, show mating preferences based on male courtship song. To test experimentally the condition dependence of courtship song, we attempted to manipulate male condition via the diet. When the diet was manipulated at the adult moult, there was no effect on subsequent male courtship song or male condition measured as residual mass. When the diet was manipulated three moults prior to the adult moult, there was a significant effect on male residual mass, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 65 publications
2
71
2
Order By: Relevance
“…Out of these, 15 studies confirmed that the sexual trait exhibited heightened sensitivity to stress in two species of cricket (Wagner & Hoback 1999;Holzer et al 2003;Scheuber et al 2003a,b), two stalk-eyed fly species (David et al 1998(David et al , 2000Knell et al 1999), wolf spiders (Kotiaho 2000), guppy fish (Sheridan & Pomiankowski 1997;Grether 2000), two species of finch (Hill & Brawner 1998;Hill 2000;McGraw & Hill 2000), the brown-headed cowbird (McGraw et al 2002) and red jungle fowl (Zuk et al 1990). Sexual traits that failed to show heightened condition dependence include components of courtship song in Gryllus crickets (Gray & Eckhardt 2001), male genital Proc. R. Soc.…”
Section: (A) General Findingsmentioning
confidence: 92%
See 1 more Smart Citation
“…Out of these, 15 studies confirmed that the sexual trait exhibited heightened sensitivity to stress in two species of cricket (Wagner & Hoback 1999;Holzer et al 2003;Scheuber et al 2003a,b), two stalk-eyed fly species (David et al 1998(David et al , 2000Knell et al 1999), wolf spiders (Kotiaho 2000), guppy fish (Sheridan & Pomiankowski 1997;Grether 2000), two species of finch (Hill & Brawner 1998;Hill 2000;McGraw & Hill 2000), the brown-headed cowbird (McGraw et al 2002) and red jungle fowl (Zuk et al 1990). Sexual traits that failed to show heightened condition dependence include components of courtship song in Gryllus crickets (Gray & Eckhardt 2001), male genital Proc. R. Soc.…”
Section: (A) General Findingsmentioning
confidence: 92%
“…Nymphal stress did not affect any other song characteristic. Courtship song has been investigated in G. texensis (Gray & Eckhardt 2001). Food treatment in nymphs and adults had no effect for any of the three courtship song parameters measured (interphase interval, chirp rate and the number of low-frequency chirps).…”
Section: (B) Cricketsmentioning
confidence: 99%
“…In another cricket species, males on restricted diets from the nymphal stage to the adult stage weighed less than males on normal diets (e.g., T. commodus; Hunt et al 2004a). Weight gained by the male cricket G. texensis during the nymphal stage under good diet conditions was greater than under poor diet conditions (Gray and Eckhardt 2001). Heavier males had more fighting ability during male-male competition (Hack 1997;Simmons 1986).…”
Section: Methodsmentioning
confidence: 98%
“…Recent evidence suggests large variation in condition dependence strength among sexually selected traits within a species (Møller and Petrie 2002). Moreover, sexually selected traits may exhibit strong condition dependence in some species (e.g., Carranza and Detrucios 1993;David et al 1998;Kotiaho 2000Kotiaho , 2002Kotiaho et al 2001;Uetz et al 2002), whereas traits with apparently similar functions are not significantly condition dependent in others (e.g., Gray and Eckhardt 2001;Perrier et al 2002). Finally, nonsexual morphological traits may also be affected by condition (see David et al 2000).…”
mentioning
confidence: 99%